2018
DOI: 10.1515/jpem-2017-0292
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic pediatric papillary thyroid carcinoma harboring the ETV6/NTRK3 fusion oncogene in a 7-year-old Japanese girl: a case report and review of literature

Abstract: Genetic evaluation showed ETV6/NTRK3 fusion but no BRAF mutations or RET/PTC rearrangements. RET/PTC rearrangement and BRAF mutations often contribute to the pathogenesis of PTC; however, rearrangements of NTRK genes are relatively rare in pediatric PTC. Although NTRK rearrangement has been shown to often present unique pathological types and infiltrative architectures in the western population, such findings were not observed in this patient. Thus, the present case of classic PTC with ETV6/NTRK3 rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The advent of selective TRK inhibitors such as larotrectinib and entrectinib showing a significant efficacy in treating advanced tumors with NTRK fusions, regardless of tumor site of origin or NTRK fusion type, has sparked great interest in NTRK genetic testing in solid tumors 3,26,27 . In addition, NTRK fusion testing might have an added prognostication value, since some studies have suggested that NTRK ‐rearranged PTCs might have more aggressive pathological features such as large, infiltrative, multifocal tumors with gross extrathyroidal extension (ETE), extensive lymphovascular invasion (LVI), and frequent nodal metastasis 21,24,28,29 . Advanced stage at presentation is common, including distant metastasis 29,30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of selective TRK inhibitors such as larotrectinib and entrectinib showing a significant efficacy in treating advanced tumors with NTRK fusions, regardless of tumor site of origin or NTRK fusion type, has sparked great interest in NTRK genetic testing in solid tumors 3,26,27 . In addition, NTRK fusion testing might have an added prognostication value, since some studies have suggested that NTRK ‐rearranged PTCs might have more aggressive pathological features such as large, infiltrative, multifocal tumors with gross extrathyroidal extension (ETE), extensive lymphovascular invasion (LVI), and frequent nodal metastasis 21,24,28,29 . Advanced stage at presentation is common, including distant metastasis 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NTRK fusion testing might have an added prognostication value, since some studies have suggested that NTRK ‐rearranged PTCs might have more aggressive pathological features such as large, infiltrative, multifocal tumors with gross extrathyroidal extension (ETE), extensive lymphovascular invasion (LVI), and frequent nodal metastasis 21,24,28,29 . Advanced stage at presentation is common, including distant metastasis 29,30 . It is therefore of utmost importance to suspect this molecular alteration to suggest molecular testing.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, FISH using break-apart probe for ETV6 or PCR with ETV6 and NTRK3 can be used to confirm morphologic suspicion. It is important to recognize, however, that ETV6-NTRK3 translocated PTC has been reported, in both radiation-and non-radiation-associated cases alike [37,[40][41][42]. Thus, the morphology and immunohistochemical features are key to distinguishing one tumor type from the other.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, one percent of cases harbor the fusion between ETV6 and NTRK3 encoding a member of the tropomyosin receptor tyrosine kinase (TRK) family [ 51 ]. This fusion is not unique of Ph-like ALL since it has been identified in a range of hematological malignancies, such as acute myeloid leukemia [ 52 ], infantile sarcoma [ 53 , 54 ] and solid tumors [ 55 , 56 , 57 , 58 ]. In preclinical models, ETV6-NTRK3 has been shown to promote the development of an aggressive B-ALL and to be exquisitely sensitive to the TRK inhibitors larotrectinib (LOXO-101) or PLX7486 (Plexxikon) in both patient derived xenograft models and in B-ALL patients with ETV6-NTRK3 [ 55 , 59 , 60 ].…”
Section: Genomic Features Of Ph-like Allmentioning
confidence: 99%